Post-radiation changes in the content of platelets in the blood and their functional activity - Parkhimovich, Olga G.; Bichan, Olga D.; Bulanova, Klavdiya Ya. (Journal of the Belarusian State University. Ecology, 2022)
The action of ionizing radiation on the body leads to the development of various pathological disorders in organs and tissues. In the first place are pathologies of the cardiovascular system. They are preceded by disorders in the blood system. There are general patterns in changes in the qualitative and quantitative composition of peripheral blood under the influence of ionizing radiation. Among cellular elements, platelets and their interaction with vascular endothelial cells play a leading role in changing the hemodynamic properties of blood. The angiotrophic function of platelets may be impaired due to changes in their number and/or functional activity. After irradiation at a dose of 1 Gy, phase changes in the number of platelets were observed in the blood of rats during the rehabilitation period. On the 3rd day of the post-radiation period, the concentration of platelets and the value of thrombocrit corresponded to those of the control group. On the 10th day, the number of platelets and the value of thrombocrit decreased in irradiated rats. In the long term after irradiation (30s and 90s), these indicators were restored to normal values. The distribution width of platelets and their average volume did not change during all the studied periods of the post-radiation period. After irradiation at a dose of 1 Gy, changes in the aggregation ability of platelets were noted when the aggregation inducer ADP was introduced at a low concentration (2.4 ± 10-6M). On the 3rd and 30th days, the irradiated sample was divided into two groups: individuals with a degree of platelet reactivity corresponding to the control, and with high reactivity. On the 10th day, among the platelets of irradiated individuals, a tendency to shift the indicators of the degree and rate of aggregation towards reduced aggregation activity prevails. In the long term (90th day) of the post-radiation period, the irradiated animals showed a prolongation of the period of change in the shape of platelets and a weakening of the reaction to aggregation inducers, which contributes to hemorrhagic manifestations. Thus, the data obtained indicate that in the short term after irradiation, the tendency to increased thrombus formation and the development of ischemic damage prevails, and in the long term (day 90), aggregation activity decreases and the risk of bleeding increases.
Keywords: platelets; irradiation; calcium metabolism; aggregation; ADP